On Speech Acts - Wijana, I Dewa Putu (Journal of Pragmatics Research, 2021)
This paper is intended to give insights to the readers about the development of speech act theories which include categories, characteristics, validities, and strategies. The research begins with the classification of speech acts done by some experts and continues with the description of characteristics and validities carried out especially by Austin and Searle, and ends with speech act strategies developed by Parker and Riley, using examples taken from Indonesian, Javanese, Balinese, and English, four languages that the writer masters relatively well. Most Indonesian, Balinese, and Javanese data together with their context are created intuitively as a native or nearly-native speaker while some English utterances are created and the others extracted from pragmatic textbooks used as references in this study. Research findings show that there are various types of speech acts, and each speech act has its own validity conditions. Among them, illocutionary acts constitute the focal point of pragmatics’ studies. The description shows that every expert of pragmatics uses different categories in classifying illocutionary acts, and the kinds of strategies used to express them.Keywords: pragmatics, speech act, speech act strategy.